TRANSFORMASI NILAI PANCASILA DALAM DINAMIKA SOSIAL MASYARAKAT MODERN - Apriyanto Ari Setiawan; Muhammad Sandi Azhar; Muhammad Syafii (Tahta Media Group, 2025)
This study aims to analyze the transformation of Pancasila values within the dynamics of modern society and to examine how students interpret these values amid globalization and digital development. The research employed a qualitative approach with a case study design conducted at MTs Kyai Abdan Magelang. Data were collected through observation, in-depth interviews, questionnaires, and document analysis involving the principal, teachers, and students. The findings indicate that students demonstrate a high level of conceptual understanding of Pancasila values (86%) and are able to relate them to school social life (82%). However, in the digital context, only 61% consistently apply value-based ethics in social media use, and 58% are capable of critically verifying information. The transformation of Pancasila values in this madrasah occurs through three main forms: pedagogical transformation via contextual learning, cultural transformation through school culture, and participatory transformation through deliberative practices and social activities. The study concludes that Pancasila values remain relevant in modern society, yet require reinforcement through digital literacy and reflective learning approaches to effectively respond to the challenges of globalization.